The Chikungunya epidemic on La Réunion Island in 2005-2006: a cost-of-illness study. - Man-Koumba Soumahoro; Pierre-Yves Boelle; Bernard-Alex Gaüzere; Kokuvi Atsou; Camille Pelat; Bruno Lambert; Guy La Ruche; Marc Gastellu-Etchegorry; Philippe Renault; Marianne Sarazin; Yazdan Yazdanpanah; Antoine Flahault; et al. (Public Library of Science (PLoS), 2011)
BACKGROUND:This study was conducted to assess the impact of chikungunya on health costs during the epidemic that occurred on La Réunion in 2005-2006. METHODOLOGY/PRINCIPAL FINDINGS:From data collected from health agencies, the additional costs incurred by chikungunya in terms of consultations, drug consumption and absence from work were determined by a comparison with the expected costs outside the epidemic period. The cost of hospitalization was estimated from data provided by the national hospitalization database for short-term care by considering all hospital stays in which the ICD-10 code A92.0 appeared. A cost-of-illness study was conducted from the perspective of the third-party payer. Direct medical costs per outpatient and inpatient case were evaluated. The costs were estimated in Euros at 2006 values. Additional reimbursements for consultations with general practitioners and drugs were estimated as € 12.4 million (range: € 7.7 million-€ 17.1 million) and € 5 million (€ 1.9 million-€ 8.1 million), respectively, while the cost of hospitalization for chikungunya was estimated to be € 8.5 million (€ 5.8 million-€ 8.7 million). Productivity costs were estimated as € 17.4 million (€ 6 million-€ 28.9 million). The medical cost of the chikungunya epidemic was estimated as € 43.9 million, 60% due to direct medical costs and 40% to indirect costs (€ 26.5 million and € 17.4 million, respectively). The direct medical cost was assessed as € 90 for each outpatient and € 2,000 for each inpatient. CONCLUSIONS/SIGNIFICANCE:The medical management of chikungunya during the epidemic on La Réunion Island was associated with an important economic burden. The estimated cost of the reported disease can be used to evaluate the cost/efficacy and cost/benefit ratios for prevention and control programmes of emerging arboviruses.